A VNIR spectral database of terrestrial magmatic rocks for the interpretation of Martian plagioclase hyperspectral detections - M. Barthez; J. Flahaut; M. Guitreau; R. Pik; G. Ito; C. Delangle; J.-P. Gremilliet; B. Luais; F. Faure (Icarus, 2026)

Repeated identification of plant-associated polerovirus 3 (PaPV3) and of a novel polerovirus in the virome of French grain cereals - L. Svanella-Dumas; A. Marais; C. Faure; B. Bergey; R. Comte; T. Candresse (Archives of Virology, 2026)

Characterization of French isolates of wheat mosaic virus and identification of multiple variants of genomic RNAs 5 and 6 - T. Candresse; L. Svanella-Dumas; Aijun Huang; C. Faure; R. Comte; A. Marais (Archives of Virology, 2026)

Northwest Africa 4269: a metal-rich eucrite from the Algerian Sahara - Abdelmadjid Seddiki; Bertrand Moine; Jérôme Bascou; Ratiba Kared; Jean Yves Cottin; Marguerite Godard; François Faure; Richard C. Greenwood; Ian A. Franchi (Geochemistry, 2025)

Structural controls on simultaneous earthquake clustering and normal fault synchronization - F. Iezzi; C. Sgambato; G. Roberts; Z. Mildon; J. Robertson; J. Faure Walker; I. Papanikolaou; A.M. Michetti; S. Mitchell; R. Shanks; R. Phillips; K.J.W. McCaffrey; et al. (Earth and Planetary Science Letters, 2025)

Characteristics and modelling of slip-rate variability and temporal earthquake clustering across a distributed network of active normal faults constrained by in situ 36Cl cosmogenic dating of fault scarp exhumation, central Italy - G.P. Roberts; F. Iezzi; C. Sgambato; J. Robertson; J. Beck; Z.K. Mildon; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; S. Mitchell; M. Meschis; R. Shanks; et al. (Journal of Structural Geology, 2025)

Ecosystem based approach to assess the impact of invasive or expanding species in the lower Saône River - T. Changeux; A. Dragotta; E. Franquet; N. Stolzenberg; J.F. Fruget; L. Marion; C. Souty-Grosset; O. Anneville; L. Cavalli; J.P. Faure; N. Corget; F. Josserand; et al. (Anthropocene, 2024)

Complete genome sequences of three Prunus-infecting nepoviruses: apricot latent ringspot virus, myrobalan latent ringspot virus, and a novel virus from smooth stone peach (Prunus mira Koehne) - M. Khalili; T. Candresse; C. Faure; Y. Brans; A. Marais (Archives of Virology, 2024)

A new geminialphasatellite associated with wheat dwarf virus identified in winter barley in France - Aijun Huang; Laurence Svanella-Dumas; C. Vitry; Armelle Marais; Chantal Faure; Thierry Candresse (Archives of Virology, 2024)

SMXL5 attenuates strigolactone signaling in Arabidopsis thaliana by inhibiting SMXL7 degradation - Qingtian Li; Haiyang Yu; Wenwen Chang; Sunhyun Chang; Michael Guzmán; Lionel Faure; Eva-Sophie Wallner; Heqin Yan; Thomas Greb; Lei Wang; Ruifeng Yao; David C. Nelson (Molecular Plant, 2024)

Spatial migration of temporal earthquake clusters driven by the transfer of differential stress between neighbouring fault/shear-zone structures - G.P. Roberts; C. Sgambato; Z.K. Mildon; F. Iezzi; J. Beck; J. Robertson; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; M. Meschis; R. Shanks; R. Phillips; et al. (Journal of Structural Geology, 2024)

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Origin of nitrogen on Mars: First in situ N isotope analyses of martian meteorites - C. Deligny; E. Füri; E. Deloule; A.H. Peslier; F. Faure; Y. Marrocchi (Geochimica et Cosmochimica Acta, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Identification of two novel putative satellite RNAs with hammerhead structures in the virome of French and Spanish carrot samples - B. M. Babalola; D. Schönegger; C. Faure; A. Marais; A. Fraile; F. Garcia-Arenal; T. Candresse (Archives of Virology, 2022)

Complete genome sequence of cherry virus T, a novel cherry-infecting tepovirus - A. Marais; D. Šafářová; M. Navrátil; C. Faure; D. Cornaggia; Y. Brans; J. Suchá; T. Candresse (Archives of Virology, 2020)

Complete genome sequence of a novel grapevine-infecting member of the genus Polerovirus, grapevine polerovirus 1 - T. Candresse; A. Marais; C. Faure; M. Lefebvre; T. Lacombe; J. M. Boursiquot (Archives of Virology, 2020)

Effect of thermal pre-treatment on the availability of PAHs for successive chemical oxidation in contaminated soils - M. Usman; A. Chaudhary; C. Biache; P. Faure; K. Hanna (Environmental Science and Pollution Research, 2016)

Treatment of hydrocarbon contamination under flow through conditions by using magnetite catalyzed chemical oxidation - M. Usman; P. Faure; C. Lorgeoux; C. Ruby; K. Hanna (Environmental Science and Pollution Research, 2013)

A green and bio-inspired process to afford durable anti-biofilm properties to stainless steel - E. Faure; C. Vreuls; C. Falentin-Daudré; G. Zocchi; C. Van de Weerdt; J. Martial; C. Jérôme; A.-S. Duwez; C. Detrembleur (Biofouling, 2012)

Biomolecule-based antibacterial coating on a stainless steel surface: multilayer film build-up optimization and stability study - C. Vreuls; G. Zocchi; H. Vandegaart; E. Faure; C. Detrembleur; Anne-Sophie Duwez; J. Martial; C. Van De Weerdt (Biofouling, 2012)

Genome-wide association analysis to identify chromosomal regions determining components of earliness in wheat - J. Le Gouis; J. Bordes; C. Ravel; E. Heumez; S. Faure; S. Praud; N. Galic; C. Remoué; F. Balfourier; V. Allard; M. Rousset (Theoretical and Applied Genetics, 2012)

Geochronological and geochemical characterization of magmatic-hydrothermal events within the Southern Variscan external domain (Cévennes area, France) - A. Chauvet; N. Volland-Tuduri; C. Lerouge; V. Bouchot; P. Monié; X. Charonnat; M. Faure (International Journal of Earth Sciences, 2012)

Field observations from the Aquila, Italy earthquake of April 6, 2009 - T. Rossetto; N. Peiris; J. E. Alarcon; E. So; S. Sargeant; M. Free; V. Sword-Daniels; D. Del Re; C. Libberton; E. Verrucci; P. Sammonds; J. Faure Walker (Bulletin of Earthquake Engineering, 2011)

Land use monitoring by remote sensing in tropical forest areas in support of the Kyoto Protocol: the case of French Guiana - N. Stach; A. Salvado; M. Petit; J. F. Faure; L. Durieux; C. Corbane; P. Joubert; D. Lasselin; M. Deshayes (International Journal of Remote Sensing, 2009)

Comparative phylogeography among hydrothermal vent species along the East Pacific Rise reveals vicariant processes and population expansion in the South - S. PLOUVIEZ; T. M. SHANK; B. FAURE; C. DAGUIN‐THIEBAUT; F. VIARD; F. H. LALLIER; D. JOLLIVET (Molecular Ecology, 2009)
The use of sequence polymorphism from individual mitochondrial genes to infer past demography has recently proved controversial because of the recurrence of selective sweeps acting over genes and the need for unlinked multilocus data sets. However, comparative analyses using several species for one gene and/or multiple genes for one species can serve as a test for potential selective effects and clarify our understanding of historical demographic effects. This study compares nucleotide polymorphisms in mitochondrial cytochrome oxidase I across seven deep‐sea hydrothermal vent species that live along the volcanically active East Pacific Rise. Approximate Bayesian Computation (ABC) method, developed to trace shared vicariant events across species pairs, indicates the occurrence of two across species divergence times, and suggests that the present geographical patterns of genetic differentiation may be explained by two periods of significant population isolation. The oldest period dates back 11.6 Ma and is associated with the vent limpet Lepetodrilus elevatus , while the most recent period of isolation is 1.3 Ma, which apparently affected all species examined and coincides with a transition zone across the equator. Moreover, significant negative Tajima’s D and star‐like networks were observed for all southern lineages, suggesting that these lineages experienced a concomitant demographic and geographical expansion about 100 000–300 000 generations ago. This expansion may have initiated from a wave of range expansions during the secondary colonization of new sites along the Southern East Pacific Rise (founder effects below the equator) or recurrent bottleneck events because of the increase of eruptive phases associated with the higher spreading rates of the ridge in this region.

Root-knot nematode (Meloidogyne spp.) Me resistance genes in pepper (Capsicum annuum L.) are clustered on the P9 chromosome - C. Djian-Caporalino; A. Fazari; M. J. Arguel; T. Vernie; C. VandeCasteele; I. Faure; G. Brunoud; L. Pijarowski; A. Palloix; V. Lefebvre; P. Abad (Theoretical and Applied Genetics, 2007)

High dietary sucrose triggers hyperinsulinemia, increases myocardial β-oxidation, reduces glycolytic flux and delays post-ischemic contractile recovery - D. Gonsolin; K. Couturier; B. Garait; S. Rondel; V. Novel-Chaté; S. Peltier; P. Faure; P. Gachon; Y. Boirie; C. Keriel; R. Favier; S. Pepe; et al. (Molecular and Cellular Biochemistry, 2007)

Corticosteroids in patients with antiovarian antibodies undergoing in vitro fertilization: a prospective pilot study - Thierry Forges; Patricia Monnier-Barbarino; Frédérique Guillet-May; Gilbert C. Faure; Marie-Christine Béné (European Journal of Clinical Pharmacology, 2006)

Epidemiology of Candidaemia in Europe: Results of 28-Month European Confederation of Medical Mycology (ECMM) Hospital-Based Surveillance Study - A. M. Tortorano; J. Peman; H. Bernhardt; L. Klingspor; C. C. Kibbler; O. Faure; E. Biraghi; E. Canton; K. Zimmermann; S. Seaton; R. Grillot (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Analysis of conserved and non-conserved amino acids critical for ALSV (Avian leukemia and sarcoma viruses) integrase functions in vitro - K. Moreau; C. Faure; G. Verdier; C. Ronfort (Archives of Virology, 2002)

Hercynian polyphase tectonics in the northeast French Massif Central: the closure of the Brévenne Devonian-Dinantian rift - C. Leloix; M. Faure; J.-L. Feybesse (International Journal of Earth Sciences, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

A simple and efficient method for in vitro shoot regeneration from leaves of lavandin ( Lavandula ×× intermedia Emeric ex Loiseleur) - S. Dronne; F. Jullien; J.-C. Caissard; O. Faure (Plant Cell Reports, 1999)

Cadmium Accumulation and Metallothionein Biosynthesis in Cyprinus carpio Tissues - C. De Conto Cinier; M. Petit-Ramel; R. Faure; M. Bortolato (Bulletin of Environmental Contamination and Toxicology, 1998)

Pharmacokinetics of intravenous methylprednisolone and oral prednisone in paediatric patients with inflammatory bowel disease during the acute phase and in remission - C. Faure; J. André; C. Pelatan; A. Munck; M. Giraud; J. P. Cèzard; E. Jacqz-Aigrain (European Journal of Clinical Pharmacology, 1998)

Desulphurisation of benzothiophene and dibenzothiophene by actinomycete organisms belonging to the genus Rhodococcus, and related taxa - Christopher Oldfield; Nicola T. Wood; Steven C. Gilbert; Frazer D. Murray; Fabrice R. Faure (Antonie van Leeuwenhoek, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)